Second-line Chemotherapy for Advanced Bladder Cancer: Taxanes Versus Vinflunine - Bilgin Demir; Ali Aytaç; Gökhan Çolak; Onur Yazdan Balçık; Ömer Acar (Acta Haematologica Oncologica Turcica)
Aim: Second-line chemotherapy in advanced urothelial carcinoma (UC) remains a significant clinical challenge, with limited high-level evidence guiding regimen selection. Vinflunine is the only agent approved by the European Medicines Agency for this setting, while taxanes are widely used off-label based on phase 2 data. Methods: We conducted a retrospective analysis of patients with metastatic bladder cancer treated at Aydın Adnan Menderes University between 2013 and 2022. Eligible patients had received at least three months of second-line chemotherapy with either vinflunine or taxane-based regimens (docetaxel or paclitaxel). Progression-free survival (PFS), overall survival (OS), objective response rate (ORR), and adverse events were compared between groups. Results: Among 38 patients receiving second-line therapy, 25 (65.8%) were treated with taxanes and 13 (34.2%) with vinflunine. Median PFS was significantly longer in the taxane group (4.9 vs. 2.2 months; p=0.001). Median OS favored taxanes numerically (13.2 vs. 4.33 months) but did not reach statistical significance (p=0.068). ORR was higher in the taxane group (52% vs. 23.1%), but the difference was not statistically significant (p=0.87). Adverse event profiles were consistent with known toxicities. Conclusion: This single-center retrospective study suggests that taxane-based regimens may offer superior PFS compared to vinflunine in the second-line treatment of advanced UC, despite the lack of statistically significant OS benefit. Given limitations in access to immunotherapy and targeted agents, cytotoxic chemotherapy remains essential, underscoring the need for further prospective trials to define optimal second-line strategies.